El precio spot de la electricidad y la inclusión de energía renovable no convencional: evidencia para Colombia (2019)
Energy transition is prevalent nowadays, and Colombia is not an exception to this pheno-menon. Energy coming from non-conventional renewable resources is one main feature of this phenomenon. Therefore, this paper evaluates the impact of this new kind of rene-wable energy resources in the Colombian wholesale electricity market. This evaluation uses a counterfactual scenario based on a structural model of energy firm’s behavior that offers 1000 MW in 2018. Results suggest that the spot price decreases on average 12.66$/KWh per day. It seems that 6.66 $/KWh is due to firms’ strategies, and 6 $/KWh is a merit order effect. In addition, results suggest that 367.32 thousand tons of carbon emis-sions would not be emitted to the environment.